Stateless Person dalam tinjauan Hukum Nasional dan Hukum Internasional di Indonesia - Khalid, Fadjri; Ardianto, Budi (Uti Possidetis: Journal of International Law, 2020)
This study aims to determine how stateless persons are regulated based on international legal instruments and national legal instruments in Indonesia. Indonesia, which is affected by globalization due to the incessant promotion of tourism, has regulations on the traffic of foreigners through Law Number 6 of 2011 concerning Immigracy and on the other hand Indonesia does not recognize the existence of Stateless Persons which is different from the regulations as stated in the Convention Relating To The Status of Stateless Persons 1954. This study aims to find out that the current regulation regarding stateless persons in Indonesia has not been specifically regulated. Although Indonesia has ratified the International Covenant on Civil and Political Rights. This shows that Indonesia has not strictly regulated and in its handling of stateless people tends to be slow which results in detention exceeding the specified threshold. As for the formulation of the problem raised, namely how to regulate Stateless People in International Law and in Indonesian immigration law and the legal consequences obtained. The research method used is a normative type by means of literature study. The results of this study indicate that the arrangement for Stateless Persons in the international sphere is different from that in Indonesia because there are no strict regulations regarding this matter.